The story of snow : the science of winter's wonder - Cassino, Mark; Nelson, Jon, Ph.D (Chronicle Books, 2009)
This book about the science of snow features photos of snow crystals in their beautiful diversity and includes how snow crystals are formed into different shapes and snow-crystal-catching instructions in the back of the book.